Bisphenol A exposure increases epididymal susceptibility to infection in mice - Yoo-Jin Park; Won-Ki Pang; Do-Yeal Ryu; Elikanah Olusayo Adegoke; Md Saidur Rahman; Myung-Geol Pang (Ecotoxicology and Environmental Safety, 2021)
Male fertility is linked with several well-orchestrated events including spermatogenesis, epididymal maturation, capacitation, the acrosome reaction, fertilization, and beyond. However, the detrimental effects of bisphenol A (BPA) on sperm maturation compared to spermatogenesis and sperm cells remain unclear. Therefore, this study was to investigate whether pubertal exposure to BPA induces male infertility via interruption of the immune response in the epididymis. CD-1 male mice (5 weeks old) were treated daily with vehicle (corn oil) and 50 mg BPA/kg-BW for 6 weeks by oral gavage. Following BPA exposure, we observed decreased intraepithelial projection of basal cells, indicative of changes to the luminal environment. We also observed decreased projection of macrophages and protrusion of apoptotic cells into the lumen induced by incomplete phagocytosis of apoptotic cells in the caput epididymis. Exposure to BPA also reduced the anti- and pro-inflammatory cytokines IL-10, IL-6, IFN-γ, and IL-7 in the epididymis, while the chemotaxis-associated cytokines CCL12, CCL17, CXCL16, and MCP-1 increased. This study suggests two possible mechanisms for BPA induction of male infertility. First, exposure to BPA may induce an imbalance of immune homeostasis by disrupting the ability of basal cells to perceive environmental changes. Second, exposure to BPA may lead to collapse of macrophage phagocytosis via downregulation of intraepithelial projection and inflammatory-related cytokines. In conclusion, the observed potential pathways can lead to autoimmune disorders such epididymitis and orchitis.